Cybernetic Philosophy, Performativity, and New Media Aesthetics. - Hatipoğlu, Özüm (Yedi, 2022)
By drawing upon philosophical repercussions of cybernetics, this article reformulates the notion of performativity in the context of new media aesthetics. It links performativity to new media aesthetics via the cybernetic notions of information processing and generating systems, recursive electronic and digital feedback loops, emergency, complexity, dynamism, and autonomously evolving systems. In doing so, I argue that the operational logic and infrastructure of new media technologies can only be understood from a performative perspective. The term performance basically refers here to the movement which governs the generation and transformation of systems by putting them into action. It is through this action that the various components and parts of a system relay and process information and produce complex interactive systems. As a result, this kind of complex interactivity leads to the emergence of new forms. It is in this way that these complex systems produce new codes, configurations, and constellations. Such a formulation constitutes my starting point to describe a hybrid framework that may eventually lead to a better understanding of the essential characteristics of new media technologies and aesthetics. The shift from single, discrete, and isolated mechanical artifacts to technological systems laid the foundations for a new kind of aesthetics, the aesthetics of information processing and generating systems. The study of the art object as a system or an environment rather than a single object is crucial to address the way in which the system itself might be conceived of as an aesthetic medium. I foreground my definition of new media in the notions of medium and mediation and discuss the aesthetic possibilities brought forth by the emergence and advancement of information and communication technologies. The method used in this article is literature review.